Binding modes of a core-extended metalloporphyrin to human telomeric DNA G-quadruplexes. Issue 8 (7th January 2015) - Rubio-Magnieto, Jenifer; Di Meo, Florent; Lo, Mamadou; Delcourt, Cécile; Clément, Sébastien; Norman, Patrick; Richeter, Sébastien; Linares, Mathieu; Surin, Mathieu
Abstract : A novel π-extended Ni II -porphyrin shows a high selectivity towards human telomeric G-quadruplexes. Abstract : The molecular recognition of human telomeric G-quadruplexes by a novel cationic π-extended Ni II -porphyrin (Ni II -TImidP4 ) is studied in aqueous solutions via (chir)optical spectroscopy, Fluorescence Resonance Energy Transfer (FRET) melting assay, and computational molecular modeling. The results are systematically compared with the recognition by a conventional meso -substituted Ni II -porphyrin (Ni II -TMPyP4 ), which allows us to pinpoint the differences in binding modes depending on the G-quadruplex topology. Importantly, FRET melting assays show the higher selectivity of Ni II -TImidP4 towards human telomeric G4 than that of Ni II -TMPyP4 .